Option a: -1
Option b: 0
Explanation:
The function [tex]f(x)=-2 x+2[/tex] and [tex]g(x)=\left(\frac{1}{3}\right)^{x}+1[/tex]
To determine the solution of [tex]-2 x+2=\left(\frac{1}{3}\right)^{x}+1[/tex] and solving the expression using lambert's form, we get the solution [tex]x=-1, x=0[/tex]
Hence, the solution to the functions [tex]f(x)=-2 x+2[/tex] and [tex]g(x)=\left(\frac{1}{3}\right)^{x}+1[/tex] are -1 and 0.
Also, by looking at the graph, we can see that, the graphs f(x) and g(x) intersect at the points [tex](-1,4)[/tex] and [tex](0,2)[/tex].
Hence, the solution to [tex]-2 x+2=\left(\frac{1}{3}\right)^{x}+1[/tex] is -1 and0.
Thus, Option a and Option b are the correct answers.